Post-operative ventricular flow dynamics following atrioventricular valve surgical and device therapies: A review. (April 2018) - Nguyen, Yen Ngoc; Ismail, Munirah; Kabinejadian, Foad; Tay, Edgar Lik Wui; Leo, Hwa Liang
Highlights: Elucidating the critical roles of cardiac vortex can expand its use as a sensitive diagnosis tool towards a potential target in therapy-design. Most current therapies performed on mitral valve significantly alter the left ventricular vortex and flow patterns. Extent of flow alteration post-procedural can be controlled by choice of therapies and procedural strategy. Right ventricular flows might possess certain fundamental differences compared to the left counterpart which deserves further research. It is essential to standardise the methods and algorithms to assess vortex in the cardiovascular research. Abstract: Intra-ventricular flow dynamics has recently emerged as an important evaluation and diagnosis tool in different cardiovascular conditions. The formation of vortex pattern during the cardiac cycle has been suggested to play important epigenetic and energy-modulation roles in cardiac remodelling, adaptations and mal-adaptations. In this new perspective, flow alterations due to different cardiovascular procedures can affect the long-term outcome of those procedures. Especially, repairs and replacements performed on atrioventricular valves are likely to exert direct impact on intra-ventricular flow pattern. In this review, current consensus around the roles of vortex dynamics in cardiac function is discussed. An overview of physiological vortex patterns found in healthy left and right ventricles as well as post-operative ventricular flow phenomenon owing to different atrioventricular valvular procedures are reviewed, followed by the summary of different vortex identification schemes used to characterise intraventricular flow. This paper also emphasises on future research directions towards a comprehensive understanding of intra-cardiac flow and its clinical relevance. The knowledge could encourage more effective pre-operative planning and better outcomes for current clinical practices.